Aluminium/silicon interactions in cereal seedlings - Vashegyi, Ágnes (Acta Biologica Szegediensis, 2002)
The objective of this study was to examine the effects of Al and Si treatments on the growth and potassium uptake of roots and transport toward the shoots of common wheat (Triticum aestivum L.), durum wheat (T. durum Desf.), triticale (xTriticosecale Wittmack) and rye (Seca/e cereale L.). Seedlings were grown hydroponically at pH 4.1 with different levels of Al and Si. Increased levels of Al in the solution reduced root growth in the order of Altolerance (rye>triticale>common wheat>durum wheat). Shoot growth was only moderately influenced at higher Al concentrations. Si in the growth solution enabled plants to overcome Al toxicity symptoms, however, different species respond differently to Si applications. In shortterm (6h) uptake experiments. Si reduced the stimulatory effect of Al on K+(86Rb) uptake of roots, which indicates a definite Al-Si interaction at the plant level.